Action selection conflict and intentional binding: An ERP study. (May 2020) - Vastano, Roberta; Ambrosini, Ettore; Ulloa, José L.; Brass, Marcel
Abstract: The fluency with which we plan and execute actions has been demonstrated to increase our sense of agency (SoA). However, the exact mechanisms how fluency influences SoA are still poorly understood. It is an open question whether this effect is primarily driven by fluency of stimulus processing, response preparation or by processes following response execution. In the current study we aim at addressing this question by measuring event-related potentials reflecting pre- and post-response mechanisms and relate them to intentional binding, a measure of implicit SoA. To manipulate the fluency of action we asked participants to perform actions that were congruent or incongruent with a visual target (a finger movement). Participants' actions triggered an auditory outcome. To measure the intentional binding effect we asked participants to estimate the time between the executed actions and the ensuing auditory effects. We found that congruent actions generated a larger intentional binding effect (i.e., stronger time compression between actions and effects) and this positively correlated with a late P300 evoked during the processing of congruent stimuli. At the action selection level, we found a larger central pre-response positivity for incongruent condition as relates to interference effects. Finally, post response mechanisms elicited a larger central negativity for incongruent responses presumably related to uncertainty. We provide new evidence on the determinants of intentional binding driven by the fluency of action, by showing that both pre and post-response mechanisms are crucial in the generation of the feelings of agency. Importantly, stimulus processing and response preparation ERPs seem to be more selectively modulated by congruency-effects given specific brain-behavioral correlations.